Impuestos a los juegos de apuesta y principios constitucionales tributarios - Fonseca Sarmiento, Carlos Alberto (2021)
In this article, the author analyzes the deficiencies detected in the tax legislation on gambling based on the tax principles set forth in article 74 of the Constitution. The author develops a concept and classification of gambling based on their technical characteristics and their regulation in Peru. The author recommends homogenizing the sectoral taxation of gambling by creating a single tax and using the same methodology.